Особливості розвитку культурної дипломатії України в сучасних умовах - Луцишин, Галина; Гончарук, Анастасія; Lutsyshyn, Halyna; Honcharuk, Anastasiia (Lviv Politechnic Publishing House, 2017)
Проаналізовано особливості розвитку культурної дипломатії України в сучасних умовах, діяльність державних та громадських інститутів культурної дипломатії. Культурна дипломатія є важливим напрямом державної політики, вона відкриває перспективи соціального, культурного та економічного розвитку держави, сприяє поширенню інформації про країну через проведення культурних і мистецьких заходів, діяльність культурних інституцій, популяризацію мистецтва, культурної спадщини. Визначено основні завдання культурної дипломатії, умови та чинники, які є важливими для її розвитку. Розглянуто діяльність українських культурно-інформаційних центрів при дипломатичних представництвах України, державних структур та громадських організацій, які розвивають культурну дипломатію.

The article dwells on features of the Ukrainian cultural diplomacy in modern conditions. Cultural diplomacy is an important direction of the state policy. It opens prospects for social, cultural and economic development of the state, promotes distribution of information about the country through conducting cultural and art events, activities of cultural institutions, promotion of arts, cultural heritage and so on. It is noted that cultural diplomacy contributes to positive image of a state in the world, promotes development and strengthening of bilateral relations. The authors analyse development of cultural diplomacy in modern European countries, including activities of such organizations as the British Council, the French Institute, the Polish Institute, the Goethe Institute in Ukraine, which are important components of diplomatic missions abroad defending foreign interests and providing cross-cultural communication. It is noted that Ukrainian cultural diplomacy has been developing since Ukraine’s independence. The processes of development of Ukrainian cultural diplomacy became more active in 2015, when the first Forum for Cultural Diplomacy in Ukraine was initiated by the Ministry of Foreign Affairs of Ukraine. In addition, the Office of Public Diplomacy was created under the MFA of Ukraine. It consisted of three departments: cultural diplomacy, image projects and media relations. Today, the main focus is on promoting the Ukrainian cinema in other countries, organising photo exhibitions, meetings with Ukrainian writers, scientists, etc. The EU countries, the USA and Canada are defined as priority directions of cultural diplomacy. In 2016, the Second Forum for Cultural Diplomacy was held in Ukraine. Particular attention is paid to analysis of the Ukrainian political institutions’ activities in the development of cultural diplomacy including the Ministry of Culture, the Ministry of Foreign Affairs, the Ministry of Youth and Sports of Ukraine, the Ministry of Education and Science, the State Committee for Television and Radio Broadcasting of Ukraine, non-governmental organizations. Representatives of the Ukrainian diaspora, including prominent scientists, cultural statesms, NGO activists, also play an important role in the development of Ukrainian cultural diplomacy.
Peculiarities of the development of Ukrainian cultural diplomacy in modern conditions
Keywords: культурна дипломатія; імідж держави; політичні інститути; міжнародна політика; неурядові організації; cultural diplomacy; image of the state; political institutions; international politics; nongovernmental organizations; 327.82